Study on Antibacterial of Chitosan/Hydroxyapatite Doped Magnesium Composite as a Material for Bone Graft Applications - Laksono, Andromeda Dwi; Jr., Teodoro A. Amatosa,; Sitorus, Hilda Pebrianti Octaviana; Asih, Wentika Putri Kusuma; Sulistijono, Sulistijono (Makara Journal of Technology, 2019)
Hydroxyapatite (HAp) is one of the constituent minerals of bone and teeth, that has been widely used for synthesizing bone graft. Due to the limitation on properties of the hydroxyapatite, it is doping with Magnesium (HAp-Mg). The addition of Chitosan (Chi) was expected to improve the antibacterial properties of HAp-Mg. The present research aims to study the influence of Chitosan with 0, 5, 15, and 25 wt% addition on biocompatibility properties of Chi/HAp-Mg composite. HAp-Mg was synthesized using the sol-gel method; meanwhile, Chi/HAp-Mg composite was manufactured by mixing Chitosan in acetic acid, and HAp-Mg was added into the mixture. The synthesized samples were characterized using XRD and SEM. In vitro antibacterial activities of the Chi/HAp-Mg composite were evaluated against Escherichia coli bacteria. Biocompatibility analysis from antibacterial activity showed that composite with the optimal composition on the addition of 15 wt% Chitosan has the best ability in inhibiting the growth of E. coli bacteria.